Arabic Language Environment and the Development of Communicative Competence among Foreign Language Learners: Evidence from an Islamic University in Brunei Darussalam: دور البيئة اللغوية العربية في تنمية الكفاية الاتصالية لدى متعلمي العربية لغةً أجنبية: أدلة من جامعة إسلامية في بروناي دار السلام - Achmad Yani; Siti Sara Binti Haji Ahmad; Rafidah Binti Abdullah; Siti Shalihah (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2026)
Developing communicative competence remains a major challenge in Arabic as a Foreign Language (AFL) education, particularly in multilingual contexts where opportunities for authentic language use are limited. This study investigates the role of the Arabic language environment in fostering communicative competence among foreign language learners at Sultan Sharif Ali Islamic University (UNISSA), Brunei Darussalam. Employing a cross-sectional descriptive–correlational quantitative design, data were collected from 22 first-year students selected through purposive sampling using a five-point Likert-scale questionnaire. Descriptive statistics, Pearson correlation, and simple linear regression were used to analyze the data. The findings indicate that the institutional Arabic language environment is generally perceived positively, with particularly strong teacher-mediated interaction (86.7%), while peer communication (71.7%) and the use of Arabic in extracurricular activities (66.7%) remain comparatively limited. Students also reported that the language environment positively supports the development of speaking (75.0%) and writing (73.3%) skills. The study argues that communicative competence is shaped by a multidimensional institutional ecosystem encompassing formal instruction, teacher interaction, peer communication, linguistic landscape, and extracurricular engagement. These findings extend current perspectives on Arabic language environments in non-Arab contexts and provide practical insights for strengthening communicative Arabic education in multilingual Islamic higher education institutions.